REDES DE BIBLIOTECA ESCOLAR NO ESPÍRITO SANTO: ESTUDO DE CASO DA REDE DE VILA VELHA - Barbosa, Eliana Terra (2021)
This study seeks to understand the changes that have been taking place in school libraries, but specifically the forms of joint action articulated in networks, bringing with them modern and innovative characteristics in the educational environment. In the Brazilian context, the theme of the school library network is little explored. However, it is noted that, in the field of Information Science and in the history of Library Science, in the last ten years, the theme has gradually gained more followers among researchers in the area, sharpening the search for a more solid understanding of how this new form of action of libraries takes place in the spheres of education systems. Within this perspective, the main objective was to analyze the formation and configuration of school library networks in the State of Espírito Santo in their organizational and pedagogical dimensions, as well as to understand how these networks can indicate the strengthening and qualification of libraries as significant learning environments. The research methodology adopted was exploratory and documentary. The analysis of the results with a qualitative approach and the case study of the municipal school library network in Vila Velha/ES were established from the mapping of libraries in the state. The guiding axes and pillars for the delineation and identity configurations of a library network in the organizational and pedagogical dimensions were evidenced based on the theoretical framework (OLIVER, 1990; NOHRIA, 1992; KLIJN, KOPPENJAN, TERMEER, 1995; MIGUELETTO, 2001, CASTELLS, 2006; CARVALHO, 2017) and in documents concerning Library Science and Education. In the discussion of the research results, it was possible to verify that one of the main successes of the constitution of the network is the articulation, as it establishes communicative and dialogic actions, aimed at cooperation between the teams, and presents actions related to the effectiveness of quality products and services to the school community. From this, the network promotes internal and external entrepreneurship for libraries, librarians and the community in general. Based on the results, it concludes that when there is the establishment of a central coordination at the headquarters of the Department of Education, there is a significant representation in educational activities, strengthening actions that reverberate in all libraries, giving visibility and recognition to the professional, in addition to leverage claims for improvement in the physical structures of libraries and renewal of the collection. The study finds that the Vila Velha network, year after year, has been consolidating with the constitution of legal documentation and compliance with legislation in the area of Library Science and Education.